Kristen dan Kenaifan Politik: Kritik atas Sikap Politik PGPI dalam Pilpres 2014 - Victor Silaen (Societas Dei: Jurnal Agama dan Masyarakat, 2015)
ABSTRACT: Politics is an aspect and a system that is very important in the lives of citizens. All citizens including Christians cannot shy away from politics, because of politics produce various public policies. Thus Christians are supposed to take part in political life, not only in the electoral arena, but also in other areas. In the event the election, churches should not be nae. Churches must wisely give political enlightenment to their congregations, instead of the other way, lead the congregation to elect candidates of certain leaders. Thus the "political letter" issued by PGPI during the 2014 Presidential Election should be criticized as nae, since the content dictated the churches under PGPI. In addition, issues brought up in the letter were entirely unfounded. It is no surprise that PGPI Chairman, Rev. Dr. Jacob Nahuway, MA, received much criticism and scorn. KEYWORDS: politics, political participation, power, nation, country, religion.